DAMPAK KEHAMILAN USIA REMAJA TERHADAP KESEHATAN IBU DAN ANAK: SYSTEMATIC REVIEW - Annisa Lidra Maribeth; Rialta Hamda; Oktavia Tri Ariani; Talitha Rahma Yumna (Nusantara Hasana Journal, 2024)
Teenage pregnancy, which is a major public health problem for mothers and childrens, is often associated with adverse health impacts, especially on maternal and child health. This study aims to analyze the impact of teenage pregnancy on maternal and child health. This systematic review uses the PRISMA-P Protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols). Studies were collected through searches on the Google Scholar data source, PubMed from 2019 to 2023. Searching for key data using the PICO-S (Population Intervention Compare Outcome - Study Design) technique, 1025 studies were found and nine studies were included in this research. From the nine studies reviewed, it was found that teenage pregnancy has an impact on maternal and child health such as obstetric complications (eclampsia, premature labor, anemia during childbirth, postpartum bleeding, hypertension in pregnancy, HELLP and LBW syndrome) and can have an impact stunting in children born. Teenage pregnancy has an impact on the health of the mother and child by causing various health complications.